Pressure-resistant antibacterial nanofiltration membrane and preparation method thereof
By adding modified copper oxide fibers and zirconium silicate fibers to the nanofiltration membrane and preparing a polyamide separation layer, the problem of insufficient pressure resistance of the nanofiltration membrane is solved, and higher pressure resistance and antibacterial ability are achieved, extending the service life and improving the water yield.
Patent Information
- Application Number
- CN202411870759.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
AI Technical Summary
The existing nanofiltration membranes are prone to rupture under high pressure conditions, resulting in insufficient pressure resistance and the unit water yield cannot be increased by increasing the operating pressure at the end of the process.
By adding modified copper oxide fibers and zirconium silicate fibers to the polyvinylidene fluoride resin, a modified polyvinylidene fluoride blended membrane is formed, and a polyamide separation layer is prepared on its surface to improve the mechanical properties and antibacterial ability of the nanofiltration membrane.
It significantly improves the pressure resistance of the nanofiltration membrane, enhances its antibacterial ability, extends its service life, and improves the unit water yield.
Smart Images

Figure CN119565389A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment membrane materials and relates to a pressure-resistant antibacterial nanofiltration membrane and a preparation method thereof. Background Art
[0002] Nanofiltration membrane is a membrane separation technology between ultrafiltration and reverse osmosis. It has the characteristics of low working pressure and high separation efficiency. It has no phase change and chemical reaction at room temperature, does not destroy biological activity, can effectively intercept divalent and high-valent ions, small organic molecules with a molecular weight higher than 200, and allows most monovalent inorganic salts to pass through. It can separate similar amino acids and proteins, and achieve the separation of high molecular weight and low molecular weight organic compounds. In terms of application, nanofiltration membrane performs well in treating slightly polluted water, and can effectively remove minerals and soluble organic pollutants in water to meet the standards for healthy drinking water. In addition, nanofiltration membranes are also used in seawater desalination, which can effectively reduce the hardness and total solid solution content of seawater.
[0003] At present, the nanofiltration membranes used in industrial applications are generally composite membranes composed of a support layer base membrane and a separation functional layer obtained by interfacial polymerization. The pressure resistance limit of common commercial nanofiltration membranes is usually around 4.5MPa. They are prone to rupture when operating under high pressure conditions, so they can only operate under low pressure conditions. The disadvantage of operating under low pressure conditions is that the permeation flux of the nanofiltration membrane is small. However, in actual operation, the osmotic pressure of high-concentration salt water is relatively large. Conventional nanofiltration membranes are difficult to increase the unit water production rate by increasing the operating pressure at the end of the process, so it is very critical to improve the pressure resistance of the nanofiltration membrane. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a pressure-resistant antibacterial nanofiltration membrane and a preparation method thereof. The nanofiltration membrane prepared by the method has excellent pressure resistance.
[0005] To achieve the above object, the present invention discloses a method for preparing a pressure-resistant antibacterial nanofiltration membrane, comprising the following steps:
[0006] 1) adding inorganic fibers to a solvent, adding a silane coupling agent after ultrasonic dispersion, and then ultrasonic dispersion to obtain a mixture;
[0007] 2) adding polyvinylidene fluoride resin and pore-forming additive to the mixture obtained in step 1), heating and stirring, standing and degassing to obtain polyvinylidene fluoride casting solution, and using the polyvinylidene fluoride casting solution to prepare a modified polyvinylidene fluoride blend membrane;
[0008] 3) preparing a polyamide separation layer on the upper surface of the modified polyvinylidene fluoride membrane, and then heating and curing it to obtain a pressure-resistant antibacterial nanofiltration membrane.
[0009] The further improvement of the method for preparing the pressure-resistant antibacterial nanofiltration membrane of the present invention is:
[0010] Furthermore, in step 2), the polyvinylidene fluoride casting solution is used to prepare a modified polyvinylidene fluoride blend membrane by adopting an immersion precipitation phase conversion method.
[0011] Furthermore, the process of preparing the polyamide separation layer on the upper surface of the modified polyvinylidene fluoride membrane is:
[0012] The upper surface of the modified polyvinylidene fluoride membrane is immersed in an aqueous solution, and then immersed in an organic solution to perform an interfacial polymerization reaction to prepare a polyamide separation layer.
[0013] Furthermore, the inorganic fiber is a modified copper oxide fiber or a modified zirconium silicate fiber, and the modification of the copper oxide fiber by yttrium or cerium is completed by an electrostatic spinning method, that is, yttrium or cerium is added to the electrostatic spinning copper-containing precursor liquid. The content of yttrium or cerium (other elements such as lanthanum and samarium) is 0.2-2% of the copper oxide content; the mass ratio of copper oxide fiber to zirconium silicate fiber is 1:1 to 9:1.
[0014] Furthermore, the ratio of the length to the diameter of the inorganic fiber is greater than or equal to 50, and the diameter of the inorganic fiber is less than or equal to 10 um.
[0015] Furthermore, the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and chloroform.
[0016] Furthermore, the silane coupling agent is one or a mixture of amino, alcohol, carboxyl and aminooxy silane.
[0017] Furthermore, the pore-forming additive is one of polyvinyl pyrrolidone and polyethylene glycol or a mixture of the two.
[0018] Furthermore, the mass of the inorganic fiber in the pressure-resistant antibacterial nanofiltration membrane is 5-15% of the mass of the polyvinylidene fluoride resin.
[0019] The invention discloses a pressure-resistant antibacterial nanofiltration membrane, which is prepared based on a preparation method of the pressure-resistant antibacterial nanofiltration membrane.
[0020] The present invention has the following beneficial effects:
[0021] In the specific operation of the pressure-resistant antibacterial nanofiltration membrane and the preparation method thereof described in the present invention, modified copper oxide fibers and zirconium silicate fibers are added to polyvinylidene fluoride resin. On the one hand, the inorganic fibers are evenly distributed in all directions after being mixed in the film, interwoven with each other, and formed into a fiber network, which greatly improves the mechanical properties of the film, especially the pressure resistance. On the other hand, the addition of inorganic fibers effectively improves the hydrophilicity of the filter membrane. At the same time, the addition of modified copper oxide fibers effectively improves the bactericidal ability of the nanofiltration membrane, and the problem of network clogging due to bacterial reproduction is not likely to occur, thereby improving the flux and service life of the filter membrane. The preparation method is simple and universal, and can be easily realized in large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0023] Figure 1 This is an electron microscope image of 1% yttrium-modified copper oxide fiber;
[0024] Figure 2 Another electron microscope image of 1% yttrium-modified copper oxide fiber. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the description of the present invention, it should be understood that the terms “include” and “comprises” indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0027] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0028] It should be further understood that the term "and / or" used in the present specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects are in an "or" relationship.
[0029] It should be understood that, although the terms first, second, third, etc. may be used to describe preset ranges, etc. in the embodiments of the present invention, these preset ranges should not be limited to these terms. These terms are only used to distinguish preset ranges from each other. For example, without departing from the scope of the embodiments of the present invention, the first preset range may also be referred to as the second preset range, and similarly, the second preset range may also be referred to as the first preset range.
[0030] The word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining" or "in response to detecting", depending on the context. Similarly, the phrases "if it is determined" or "if (stated condition or event) is detected" may be interpreted as "when it is determined" or "in response to determining" or "when detecting (stated condition or event)" or "in response to detecting (stated condition or event)", depending on the context.
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.
[0033] The method for preparing the pressure-resistant antibacterial nanofiltration membrane of the present invention comprises the following steps:
[0034] 1) adding inorganic fibers to a solvent, adding a silane coupling agent after ultrasonic dispersion, and then ultrasonic dispersion to obtain a mixture;
[0035] 2) adding polyvinylidene fluoride resin and pore-forming additive to the mixture obtained in step 1), heating and stirring, standing and degassing to obtain polyvinylidene fluoride casting solution, and using the polyvinylidene fluoride casting solution to prepare a modified polyvinylidene fluoride blend membrane by immersion precipitation phase inversion method;
[0036] 3) soaking the upper surface of the modified polyvinylidene fluoride membrane in an aqueous solution, and then soaking the upper surface of the modified polyvinylidene fluoride membrane in an organic solution to perform interfacial polymerization to prepare a polyamide separation layer, which is then placed in an oven for heating and curing to obtain a pressure-resistant antibacterial nanofiltration membrane.
[0037] In the present invention, the inorganic fiber is a modified copper oxide fiber (cerium or yttrium improves the mechanical properties of copper oxide by refining the grains and promoting lattice distortion) or a zirconium silicate fiber (zirconium silicate is used as a refractory material because of its stable properties. In addition, it is used as a reinforcing phase to improve the mechanical properties of the material. For example, adding zirconium silicate to ceramics can significantly improve its bending resistance). The ratio of the length to the diameter of the fiber is greater than or equal to 50, and the diameter is less than or equal to 10um. The modification of the copper oxide fiber by yttrium or cerium is achieved by an electrospinning method, that is, yttrium or cerium is added to the electrospinning copper-containing precursor liquid.
[0038] In this embodiment, the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and chloroform, and the comparative embodiment uses N,N-dimethylacetamide.
[0039] In this embodiment, the silane coupling agent is one or a mixture of amino, alcohol, carboxyl and aminooxy silanes, and the comparative embodiment uses γ-aminopropyltriethoxysilane.
[0040] In this embodiment, the pore-forming additive is one of polyvinyl pyrrolidone and polyethylene glycol or a mixture of the two. The comparative embodiment uses polyvinyl pyrrolidone.
[0041] The content of yttrium or cerium in the copper oxide fiber is 0.2-2% of the content of copper oxide; the mass ratio of copper oxide fiber to zirconium silicate fiber is 1:1-9:1, and the mass of inorganic fiber in the pressure-resistant antibacterial nanofiltration membrane is 5-15% of the mass of polyvinylidene fluoride resin.
[0042] Comparative Example 1
[0043] This comparative example comprises the following steps:
[0044] 1) Add 2 g of copper oxide powder (10 μm) to 75 g of N,N-dimethylacetamide (DMAc) solvent, and disperse by ultrasonic for 30 min. Then, add 0.1 g of γ-aminopropyltriethoxysilane and continue to disperse by ultrasonic for 1 h.
[0045] 2) adding 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heating at 70°C and stirring for 8h, standing for 12h and degassing to obtain a polyvinylidene fluoride casting solution, scraping with a scraper on a clean glass plate to form a liquid film with an average thickness of about 200μm, standing for 30s in air with a humidity of 60%, and then immersing in a 25°C distilled water coagulation bath to form a film, then rinsing with deionized water and soaking for more than 24h, mainly to remove the residual solvent in the membrane pores, and finally obtaining a modified polyvinylidene fluoride membrane;
[0046] 3) The upper surface of the modified polyvinylidene fluoride membrane is immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane is immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer, and finally the membrane is placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0047] Comparative Example 2
[0048] The process of this comparative example is:
[0049] 1) Add 2 g of copper oxide fiber to 75 g of solvent N,N-dimethylacetamide (DMAc), disperse by ultrasonic for 30 min, then add 0.1 g of γ-aminopropyltriethoxysilane and continue to disperse by ultrasonic for 1 h;
[0050] 2) adding 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heating to 70°C and stirring for more than 8h, standing for 12h and degassing to obtain a polyvinylidene fluoride casting solution, using a scraper to scrape a liquid film with an average thickness of about 200μm on a clean glass plate, standing for 30s in air with a humidity of 60%, and then immersing in a 25°C distilled water coagulation bath to form a film, and then rinsing with ionized water and soaking for more than 24h, mainly to remove the residual solvent in the membrane pores, and finally obtaining a modified polyvinylidene fluoride membrane;
[0051] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0052] Embodiment 1
[0053] The operation process of this embodiment is as follows:
[0054] 1) 2 g of yttrium-modified copper oxide fiber (1% yttrium) was added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for another 1 h;
[0055] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and degas, obtain polyvinylidene fluoride casting liquid, use a scraper to scrape on a clean glass plate to form a liquid film with an average thickness of 200μm, stand in air with a humidity of 60% for 30s, immerse in a 25°C distilled water coagulation bath to form a film, then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and obtain a modified polyvinylidene fluoride membrane;
[0056] 3) The upper surface of the modified polyvinylidene fluoride membrane is immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane is immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane is placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0057] Embodiment 2
[0058] The operation process of this embodiment is as follows:
[0059] 1) 2 g of cerium-modified copper oxide fiber (1% cerium) was added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for another 1 h;
[0060] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and degas, obtain polyvinylidene fluoride casting solution, use a scraper to scrape on a clean glass plate to form a liquid film with an average thickness of 200μm, stand in air with a humidity of 60% for 30s, immerse in a 25°C distilled water coagulation bath to form a film, then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and obtain a modified polyvinylidene fluoride membrane;
[0061] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0062] Embodiment 3
[0063] The operation process of this embodiment is as follows:
[0064] 1) 1 g of yttrium-modified copper oxide fiber (1% yttrium) and 1 g of zirconium silicate fiber were added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for another 1 h;
[0065] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and degas, obtain polyvinylidene fluoride casting liquid, use a scraper to scrape on a clean glass plate to form a liquid film with an average thickness of about 200μm, stand in air with a humidity of 60% for 30s, immerse in a distilled water coagulation bath at 25°C to form a film, then rinse with deionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and finally obtain a modified polyvinylidene fluoride membrane;
[0066] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0067] Embodiment 4
[0068] The operation process of this embodiment is as follows:
[0069] 1) 1.67 g of yttrium-modified copper oxide fiber (1% yttrium) and 0.33 g of zirconium silicate fiber were added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for 1 h;
[0070] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and then degas, to obtain a polyvinylidene fluoride casting liquid, and then use a scraper to scrape it on a clean glass plate to form a liquid film with an average thickness of about 200μm, stand for 30s in air with a humidity of 60%, and then immerse it in a distilled water coagulation bath at 25°C to form a film, and then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and finally obtain a modified polyvinylidene fluoride membrane;
[0071] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0072] Embodiment 5
[0073] The operation process of this embodiment is as follows:
[0074] 1) 1.8 g of yttrium-modified copper oxide fiber (1% yttrium) and 0.2 g of zirconium silicate fiber were added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, and then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for 1 h;
[0075] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and degas, obtain polyvinylidene fluoride casting liquid, use a scraper to scrape on a clean glass plate to form a liquid film with an average thickness of about 200μm, stand in air with a humidity of 60% for 30s, immerse in a 25°C distilled water coagulation bath to form a film, then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and obtain a modified polyvinylidene fluoride membrane;
[0076] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0077] Embodiment 6
[0078] The operation process of this embodiment is as follows:
[0079] 1) 0.83 g of yttrium-modified copper oxide fiber (1% yttrium) and 0.17 g of zirconium silicate fiber were added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for 1 h;
[0080] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and then degas, to obtain a polyvinylidene fluoride casting liquid, use a scraper to scrape it on a clean glass plate to form a liquid film with an average thickness of about 200μm, stand in air with a humidity of 60% for 30s, immerse in a 25°C distilled water coagulation bath to form a film, and then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and obtain a modified polyvinylidene fluoride membrane;
[0081] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0082] Embodiment 7
[0083] The operation process of this embodiment is as follows:
[0084] 1) 2.5 g of yttrium-modified copper oxide fiber (1% yttrium) and 0.5 g of zirconium silicate fiber were added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for 1 h;
[0085] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and then degas, to obtain a polyvinylidene fluoride casting liquid, use a scraper to scrape it on a clean glass plate to form a liquid film with an average thickness of about 200μm, stand in air with a humidity of 60% for 30s, immerse in a 25°C distilled water coagulation bath to form a film, and then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and obtain a modified polyvinylidene fluoride membrane;
[0086] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0087] Embodiment 8
[0088] The operation process of this embodiment is as follows:
[0089] 1) 1.67 g of cerium-modified copper oxide fiber (0.2% cerium) and 0.33 g of zirconium silicate fiber were added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for 1 h;
[0090] 2) Add 20g of dried polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and then degas, to obtain a polyvinylidene fluoride casting liquid, use a scraper to scrape it on a clean glass plate to form a liquid film with an average thickness of about 200μm, stand in air with a humidity of 60% for 30s, immerse in a 25°C distilled water coagulation bath to form a film, and then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and obtain a modified polyvinylidene fluoride membrane;
[0091] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0092] Embodiment 9
[0093] The operation process of this embodiment is as follows:
[0094] 1) 1.67 g of cerium-modified copper oxide fiber (2% cerium) and 0.33 g of zirconium silicate fiber were added to 75 g of solvent N,N-dimethylacetamide (DMAc), and ultrasonically dispersed for 30 min, then 0.1 g of γ-aminopropyltriethoxysilane was added and ultrasonically dispersed for 1 h;
[0095] 2) Add 20g of dry polyvinylidene fluoride resin and 3g of polyvinyl pyrrolidone to the mixture obtained in step 1), heat at 70°C and stir for more than 8h until a uniform state is formed, stand for 12h and then degas, and after obtaining a polyvinylidene fluoride casting liquid, use a scraper to scrape it on a clean glass plate to form a liquid film with an average thickness of about 200μm, stand for 30s in air with a humidity of 60%, immerse it in a distilled water coagulation bath at 25°C to form a film, and then rinse with ionized water and soak for more than 24h, mainly to remove the residual solvent in the membrane pores, and obtain a modified polyvinylidene fluoride membrane;
[0096] 3) The upper surface of the modified polyvinylidene fluoride membrane was immersed in a 2% piperazine aqueous solution for 10 minutes, and then the upper surface of the membrane was immersed in a 0.2% trimesoyl chloride-n-hexane solution for 2 minutes to perform an interfacial polymerization reaction to prepare a polyamide separation layer. Finally, the membrane was placed in an oven for heating and curing to obtain a polyvinylidene fluoride composite nanofiltration membrane.
[0097] Nanofiltration membrane evaluation test: The standard method of “Nanofiltration Membrane Test Method” (GB / T 34242-2017) was used to test the removal rates of polyethylene glycol (PEG molecular weight 600) and magnesium sulfate respectively.
[0098] Among them, the removal rate R is calculated according to the following formula:
[0099] R=100×(Cf-Cp) / Cf
[0100] Where, R is the removal rate (%); Cf is the feed concentration (mg / L); Cp is the excess concentration (mg / L)
[0101] The test method for pressure resistance (critical pressure P) is: gradually increase the pressure test pressure from low to high, and continuously run for a period of time under the corresponding pressure. The pressure when the pure water flux of the membrane shows obvious attenuation is taken as the critical pressure P of the membrane.
[0102] The test results are shown in Table 1.
[0103] Table 1
[0104]
[0105] Through the analysis of the test data in Table 1, it can be concluded that: compared with copper oxide powder, the pressure resistance of the nanofiltration membrane prepared by adding copper oxide fibers is increased from 2.8 MPa to 3.6 MPa; and the pressure resistance of the copper oxide fiber nanofiltration membrane prepared by yttrium or cerium modification can be increased to above 4.7 MPa. By simultaneously adding yttrium or cerium modified copper oxide fibers and zirconium silicate fibers, the pressure resistance of the nanofiltration membrane can reach above 6.1 MPa, and the highest is 8.2 MPa; in addition, the nanofiltration membranes prepared in the comparative example and the embodiment have good retention rates for polyethylene glycol (PEG molecular weight 600) and magnesium sulfate, with a minimum of 96.2% and a maximum of 99.5%. Overall, the simultaneous addition of yttrium or cerium modified copper oxide fibers and zirconium silicate fibers can significantly improve the pressure resistance of the nanofiltration membrane.
[0106] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and disclosure of the invention. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0107] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a pressure-resistant antibacterial nanofiltration membrane, characterized in that: The following steps are involved: 1) adding inorganic fibers to a solvent, adding a silane coupling agent after ultrasonic dispersion, and then ultrasonic dispersion to obtain a mixture; 2) adding polyvinylidene fluoride resin and pore-forming additive to the mixture obtained in step 1), heating and stirring, standing and degassing to obtain polyvinylidene fluoride casting solution, and using the polyvinylidene fluoride casting solution to prepare a modified polyvinylidene fluoride blend membrane; 3) preparing a polyamide separation layer on the upper surface of the modified polyvinylidene fluoride membrane, and then heating and curing it to obtain a pressure-resistant antibacterial nanofiltration membrane.
2. The method for preparing a pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: In step 2), the polyvinylidene fluoride casting solution is used to prepare a modified polyvinylidene fluoride blend membrane by adopting an immersion precipitation phase conversion method.
3. The method for preparing the pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: The process of preparing the polyamide separation layer on the upper surface of the modified polyvinylidene fluoride membrane is as follows: The upper surface of the modified polyvinylidene fluoride membrane is immersed in an aqueous solution, and then immersed in an organic solution to perform an interfacial polymerization reaction to prepare a polyamide separation layer.
4. The method for preparing a pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: The inorganic fiber is modified copper oxide fiber or modified zirconium silicate fiber. The modification of copper oxide fiber by yttrium or cerium is completed by an electrostatic spinning method, that is, yttrium or cerium is added to an electrostatic spinning copper-containing precursor liquid; the yttrium or cerium content is 0.2-2% of the copper oxide content; the mass ratio of copper oxide fiber to zirconium silicate fiber is 1:1 to 9:
1.
5. The method for preparing the pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: The ratio of the length to the diameter of the inorganic fiber is greater than or equal to 50, and the diameter of the inorganic fiber is less than or equal to 10 um.
6. The method for preparing a pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: The solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and chloroform.
7. The method for preparing a pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: The silane coupling agent is one or a mixture of amino, alcohol, carboxyl and aminooxy silane.
8. The method for preparing a pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: The pore-forming additive is one of polyvinyl pyrrolidone and polyethylene glycol or a mixture of the two.
9. The method for preparing a pressure-resistant antibacterial nanofiltration membrane according to claim 1, characterized in that: The mass of the inorganic fiber in the pressure-resistant antibacterial nanofiltration membrane is 5-15% of the mass of the polyvinylidene fluoride resin.
10. A pressure-resistant antibacterial nanofiltration membrane, characterized in that: The pressure-resistant antibacterial nanofiltration membrane is prepared based on the preparation method of any one of claims 1 to 9.